THE EFFECT OF WORKLOAD, COMPETENCE AND INFORMATION TECHNOLOGY ON THE PERFORMANCE OF GUGUS IMPLEMENTERS QUALITY CONTROL THROUGH JOB SATISFACTION AS A MEANS MEDIATION VARIABLES - Haryani Tri Puteri Hasman; Yeni Absah; Prihatin Lumbanraja (CV. Radja Publika, 2024)
University Sumatera Utara is a State University with Legal Entity (PTN-BH) established by the government and has the status of an autonomous public legal entity. Every university is required to have Quality Assurance in the Study Program, quality assurance in the Study Program is evaluated by the implementer of the Quality Control Group (GKM) of the Study Program. Currently, the performance of the GKM Implementer is not achieved. This study aims to determine the effect of Workload, Competence and Information Technology on the Performance of the Implementer of the Quality Control Group of the Study Program with Job Satisfaction as a mediating variable. The subjects used in this study were the Implementers of the GKM Study Program at University Sumatera Utara. The number of samples taken in this study was 130 respondents. The data obtained were from the results of distributing questionnaires via google form using purposive sampling techniques. The processing of the collected data was carried out using the SmartPLS program. Based on the results of data analysis, it can be concluded that Workload has a positive and significant effect on Job Satisfaction, Competence has a positive and significant effect on Job Satisfaction, Information Technology has a positive and significant effect on Job Satisfaction, Workload has a positive and insignificant effect on the performance of GKM Implementers, Competence has a positive and significant effect on the performance of GKM Implementers, Information Technology has a positive and insignificant effect on the performance of GKM Implementers, Job satisfaction has a positive and significant effect on the performance of GKM Implementers, workload has a positive and significant effect on the performance of GKM implementers through job satisfaction, competence has a positive and significant effect on the performance of GKM implementers through job satisfaction, information technology has a positive and significant effect on the performance of GKM implementers through job satisfaction.